Research on Disaster Resilience Measurement and Its Differential Patterns in Southern Jiangsu Cities - Huang, Man (International Journal of Natural Resources and Environmental Studies, 2024)
As an important carrier of human social development, how to improve the response speed and adaptability of urban systems under uncertain factors such as disasters is currently a hot topic in international research. Based on panel data from the southern Jiangsu region from 2011 to 2020, this paper uses the entropy method to measure the resilience levels of various cities, analyzes the factors hindering urban resilience using the resilience barrier model, and explores regional resilience development differences through resilience spatial visualization analysis. The results show: (1) The overall level of urban resilience in the southern Jiangsu region presents a spatial distribution pattern of high in the east, low in the central region, and significant differences in urban resilience; (2) The ranking of urban resilience barriers in southern Jiangsu from 2011 to 2020 is: social resilience, infrastructure resilience, economic resilience, ecological resilience; (3) From the indicator level, factors such as the number of ordinary colleges and universities, total urban water supply, and general public budget revenue have a significant impact on the urban resilience barrier in southern Jiangsu. To enhance urban resilience, it is necessary to optimize the layout structure of higher education, improve urban infrastructure, and strengthen the synergy of urban construction.